Filters and ideals in a fuzzy lattice - Saadi, Djazia (UNIVERSITE MOHAMED BOUDIAF - M’SILA- FACULTE MATHEMATIQUES ET DE L’INFORMATIQUE, 2019)
In this memory, we will study some characterizations of filters, ideals, fuzzy filters, fuzzy ideals, α-filters, α-ideals, prime filters and prime ideals of a fuzzy lattice. We will recall the notion of isomorphism between fuzzy lattices, also the converse image of a fuzzy prime filter will be characterized via an isomorphism.
Keywords: Fuzzy lattice, fuzzy filter, fuzzy ideal, α-filter, α-ideal, lattices homomorphism.